Núcleos de osificación epifisiarios para la predicción de la gestación a término en pacientes con cesárea electiva - Olortegui Espinoza, Miguel (2014)
To demonstrate that the presence and sum of the diameters of the nucleus of epiphysial ossification of long bones is effective in term pregnancy diagnosis and differentiation between term newborn premature and full-term in patients undergoing elective cesarean section. Material and Methods: Prospective analytical observational cohort study, which evaluated 52 patients treated at the Gynecology Service of Hospital Regional Docente de Trujillo in the period November 2013 to April 2014; the newborns (NB) were evaluated early term and full term. Femur, tibia, humerus: the presence, extent and summation of the nucleus bone ossification was determined. Results: The extent of distal femoral nuclei ossification (NOFD)> 4 mm as a diagnostic test for predicting 39-41 weeks gestation, has a sensitivity: 93.1% (78 to 98.1); Specificity: 34.8% (18.8 to 55.1), PPV: 64.3% (49.2 to 77.0), NPV: 80% (49 to 94.3), LR +: 1.43 (1.04 to 1.96), LR -: 0.20 (0.05 to 0.80), with p: 0.015. No statistical significance was found as a diagnostic test to analyze the sum of ossification centers of > 6 mm. NODF correlation with EG by physical examination was found with a p value 0.02 and a coefficient of determination of 0.18. No correlation was found with statistical significance between NODF and birth weight. Correlation between the sum of ossification centers and gestational age by physical examination was found with a p value of 0.04 and a coefficient of determination of 0.15. No correlation was found with statistical significance between the sum of ossification nuclei and birth weight. Conclusion: The measurement of fetal epiphysial ossification nuclei is effective in predicting term gestation, allowing differentiation between RN to early and full-term